Impacts of Louisiana Public Policy on Employment: An Econometric Analysis - Frazier, Russell M. (Advances in Social Sciences Research Journal, 2019)
Employment plays a key role in the growth and development of any state economy, particularly given its potential to affect the standards of living for the population, as well as the revenues and expenditure of the government itself. A disaggregated evaluation of employment growth enables stakeholders to engage public policy formation in a more effective and efficacious manner. Therefore, the primary goal of this paper is to analyze employment growth trends and policy implications relative to the economic development of Louisiana’s industries at the sector level, by employing a rigorous shift-share analysis. The research employs data for twelve years from 2005 to 2017 to answer the guiding questions of this applied empirical research. Results show that comparative advantages are seen in the following areas: Finance and Insurance; Real Estate and Rental and Leasing; Administrative and Waste Services; Educational Services; Accommodation and Food Services; and Other Services (except for Public Administration). Thus, program initiatives directed at those sectors, with sufficient infrastructure, would enhance the economic development of Louisiana. It is plausible to believe that improved economic growth would draw new investors to Louisiana.